Interconversion between Anticipatory and Active GID E3 Ubiquitin Ligase Conformations via Metabolically Driven Substrate Receptor Assembly - Qiao, Shuai; Langlois, Christine R; Chrustowicz, Jakub; Sherpa, Dawafuti; Karayel, Ozge; Hansen, Fynn M; Beier, Viola; Susanne Von Gronau; Bollschweiler, Daniel; Schafer, Tillman; Alpi, Arno F; Mann, Matthias; et al. (bioRxiv, 2019)
Cells respond to environmental changes by toggling metabolic pathways, preparing for homeostasis, and anticipating future stresses. For example, in Saccharomyces cerevisiae, carbon stress-induced gluconeogenesis is terminated upon glucose availability, a process that involves the multiprotein E3 ligase, GIDSR4, recruiting N-termini and catalyzing ubiquitylation of gluconeogenic enzymes. Here, genetics, biochemistry, and cryo electron microscopy define molecular underpinnings of glucose-induced degradation. Unexpectedly, carbon stress induces an inactive anticipatory complex (GIDAnt), which awaits a glucose-induced substrate receptor to form the active GIDSR4. Meanwhile, other environmental perturbations elicit production of an alternative substrate receptor assembling into a related E3 ligase complex. The intricate structure of GIDAnt enables anticipating and ultimately binding various N-degron targeting (i.e. "N-end rule") substrate receptors, while the GIDSR4 E3 forms a clamp-like structure juxtaposing substrate lysines with the ubiquitylation active site. The data reveal evolutionarily conserved GID complexes as a family of multisubunit E3 ubiquitin ligases responsive to extracellular stimuli.